Vintage article: the effect of monetary policy shocks in the UK: an external instruments approach - Görtz, C; Li, W; Tsoukalas, J; Zanetti, F (Cambridge University Press, 2023)
This paper uses vector autoregression model analysis to identify monetary policy shocks on UK data using surprise changes in the policy rate as external instruments and imposing block exogeneity restrictions on domestic variables to estimate parameters from the viewpoint of the domestic economy. The results show large and persistent effects of monetary policy shocks on the domestic economy and point to the critical role of exchange rates and term premia. The analysis resolves important empirical puzzles of traditional recursive identification methods.